(untitled) (Journal of Engineering, 2006)
Gypseous soils can be found in arid and semi arid region. In civil engineering it can be defined that a soil is a gypseous soil when it has gypsum content enough to change the properties of this soil. Collapsibility of these soils was found to be of major importance. The collapsibility of the soil can be estimated from the term "Collapse Potential (CP)" which can be obtained from two types of tests performed in the oedometer device; (1) Single Collapse Test (SCT) and (2) Double Oedometer Test (DOT). In this study, an analysis of the results obtained by 7 researchers in Iraq was performed. The data collected included basic properties for each sample in addition to the results of the two collapsibility tests. A total of 50 samples were analyzed and it was noticed that 33 % of the investigated soils have a CP less than 1% which are considered as "No Trouble" soils and about 60% have a CP ranging between 1 and 5 which are considered as "moderate trouble" soils. The factors affecting collapsibility were studied and it appeared that the initial water content, void ratio and total unit weight are the major factors while the gypsum content and plasticity index seem to have lesser effect. Three proposed equations are introduced to estimate CP at 200 kPa as obtained from (SCT) from other parameters. These equations are: (1) CP from (DOT) (2) CP from different soaking pressures and (3) CP from basic soil properties (initial water content, void ratio and gypsum content). These equations have a regression (R-squared) ranging between 0.7 and 0.85